Internal and external factors of providing quality traditional health services in public health centres in Tabanan District, Bali, Indonesia - I Wayan Murdita; Dyah Pradnyaparamita Duarsa; I Nyoman Hariyasa Sanjaya (Universitas Udayana, 2020)
Background and purpose: Traditional health services has beenintegrated into health services at the public health center (PHC),however, its implementation remains suboptimal. Situational analysis is required to identify implementation factors of traditional health services. This study aims to explore key strengths, weaknesses, opportunities and threats of providing quality traditional health services at PHCs in Tabanan District. Methods: A qualitative study using an explorative case study design was conducted across PHCs in Tabanan District between January and February 2020. We utilized a SWOT analysis framework to facilitate our study. Data were collected through semi-structured in-depth interviews with 14 informants. They were purposively selected to allow rich data being collected. Six informants were considered as key informants and eight informants were considered as supporting informants. Data were analyzed using thematic approach. Results: The strengths of PHCs in Tabanan District to provide quality traditional health services include commitment and competency of health providers, trust towards traditional medicine from health staff and community members, promotional activities, the tariff scheme and an established partnership with traditional healers. The weaknesses include limited numbers of staff, high workload of existing health providers and lack of supporting facilities and financial assistance. The opportunities include support from the community, the potency of traditional medicines, availability of government regulations, an established collaboration between traditional and conventional health services and potential customers brought by tourism industries of Bali Province. The threats include unlicensed traditional healers, lack of support from local governments and irresponsible promotional conducts. Conclusion: Our study reveals key strengths, weaknesses, opportunities and threats of providing quality traditional health services at the PHC level in Tabanan District. Findings from our SWOT analysis can be used to develop strategies for improving implementation of traditional health services at the PHC level.